The effectiveness of using the conversion ladder on the critical thinking skills of grade III students at Elementary School 36 South Pontianak - Salsa Wulandari; Agung Hartoyo; Y. Touvan Juni Samodra; Procopio B. Dafun JR (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Elementary school students’ critical thinking skills in learning length unit conversions remain relatively low and require concrete instructional support. This study examined the effectiveness of conversion ladder media in improving third-grade students' critical thinking skills at elementary school 36 South Pontianak. A one-group pretest–posttest design was employed with 24 students selected through purposive sampling. Data were collected using a matching test based on six critical thinking indicators proposed by Facione. The Wilcoxon test revealed a significant improvement (p = 0.001 < 0.05), with mean scores increasing from 30.83 (pretest) to 76.46 (posttest). An effect size of 1.95 indicated a high level of effectiveness. These findings demonstrate that conversion ladder media effectively enhance elementary school students’ critical thinking skills in mathematics.